Comparison of Diagnostic Value between Point of Care Testing (POCT) and Standardize HbA1c Testing in Primary Health Care - Rudijanto, Achmad; Rosandi, Rulli; Sasiarini, Laksmi (Clinical and Research Journal in Internal Medicine, 2020)
Diabetes Mellitus is one of the biggest health problems. HbA1c is used to diagnose, to monitor treatment and treatment adjustment. High Performance Liquid Chromatography (HPLC) and electron spray mass spectrometry are recommended to measure HbA1c. But both methods need expensive cost, facility, and potentially increase health cost burden. HbA1c measurement using Point of Care Testing (POCT) is developed in Indonesia. POCT is more comfortable, has lower cost and easily brought to primary health care. Aim: to assess the clinical efficacy of POCT compared with a standard examination by HPLC. Methods: It is a cross-sectional observational study conducted at a first-level health facility (FKTP) in Malang. The subject population was patients who went to an outpatient unit in FKTP with inclusion criteria aged 20-75 years, were participants in the chronic disease management program (PROLANIS), both diabetes and non-diabetes. Results: Three hundred and thirty eight subjects were participated in this study. Five subjects were excluded because the presence of anemia. We used Wilcoxon test to compare HbA1c level between two methods and Rank Spearman correlation test to find correlation between two methods. This study showed measurement HbA1c level using POCT method had good accuracy (>80%). Other than diagnosis value, increased utilization of POCT HbA1c might also be caused by its portability and patient’s comfort. Conclusions: This study showed a strong correlation (R=0.016) between POCT HbA1c and standardized measurement. POCT HbA1c also showed good accuracy in all HbA1c groups.